Azvudine, a novel nucleoside reverse transcriptase inhibitor showed good drug combination features and better inhibition on drug-resistant strains than lamivudine in vitro. - Rui-Rui Wang (Public Library of Science (PLoS), 2014)
Azvudine is a novel nucleoside reverse transcriptase inhibitor with antiviral activity on human immunodeficiency virus, hepatitis B virus and hepatitis C virus. Here we reported the in vitro activity of azvudine against HIV-1 and HIV-2 when used alone or in combination with other antiretroviral drugs and its drug resistance features. Azvudine exerted highly potent inhibition on HIV-1 (EC(50)s ranging from 0.03 to 6.92 nM) and HIV-2 (EC(50)s ranging from 0.018 to 0.025 nM). It also showed synergism in combination with six approved anti-HIV drugs on both C8166 and PBMC. In combination assay, the concentrations of azvudine used were 1000 or 500 fold lower than other drugs. Azvudine also showed potent inhibition on NRTI-resistant strains (L74V and T69N). Although M184V caused 250 fold reduction in susceptibility, azvudine remained active at nanomolar range. In in vitro induced resistant assay, the frequency of M184I mutation increased with induction time which suggests M184I as the key mutation in azvudine treatment. As control, lamivudine treatment resulted in a higher frequency of M184I/V given the same induction time and higher occurrence of M184V was found. Molecular modeling analysis suggests that steric hindrance is more pronounced in mutant M184I than M184V due to the azido group of azvudine. The present data demonstrates the potential of azvudine as a complementary drug to current anti-HIV drugs. M184I should be the key mutation, however, azvudine still remains active on HIV-1LAI-M184V at nanomolar range.